The Role of Audit Opinion in Enhancing the Influence of Local Revenue and Capital Expenditure on the Financial Performance of Local Governments in Indonesia - Ira Teja Sukma; Raden Budi Hendaris (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study examines the moderating role of audit opinion in strengthening the influence of Local Own-Source Revenue (PAD) and capital expenditure on the financial performance of local governments in Indonesia. Using secondary data from 508 regencies and cities over the 2019–2023 period, the research makes use of Moderated Regression Analysis (MRA) not just as a statistical tool, but as a way to uncover how one variable can bend, boost, or blur the effect of another.The data flows in from two solid sources: the Directorate General of Fiscal Balance and the Audit Board of the Republic of Indonesia. In essence, it’s like connecting two streams of credible insight to see how they dance together numbers turning into patterns, and patterns unfolding into meaning. The results reveal that PAD has a positive and significant effect on local financial performance, indicating that higher local revenues improve fiscal independence and efficiency in regional financial management. In contrast, capital expenditure does not significantly influence financial performance, suggesting that increased investment in assets has not been optimally managed to produce productive outcomes. Furthermore, audit opinion strengthens the relationship between PAD and financial performance, but not between capital expenditure and financial performance. This implies that sound financial governance and compliance, reflected in favorable audit opinions, enhance the effectiveness of local revenue management. The findings emphasize the strategic role of accountability and transparency in promoting sustainable regional fiscal performance.